PENGARUH PENGEMBANGAN KARIER, KOMPETENSI DAN TUNJANGAN KINERJA TERHADAP PENINGKATAN KINERJA PEGAWAI PADA DINAS PERHUBUNGAN KOTA MOJOKERTO - Indriswari, Tiyas; Hartono, Hartono; Kasnowo, Kasnowo (LP2M Universitas Bina Bangsa, 2024)
In the era of globalization and increasing competition, public sector organizations such as the Mojokerto City Transportation Office are required to enhance service quality and employee productivity to meet various changes and challenges. Employee performance is crucial as it reflects the organization's human resource effectiveness, with employees being its key assets. Therefore, managing and optimizing human resources is imperative for organizational success. Human resources play a pivotal role, supported and complemented by other factors in achieving organizational goals. This study examines whether career development, competence, and performance allowance have partial or simultaneous effects on employee performance improvement, and identifies which variables predominantly influence employee performance. The research aims to analyze the partial and simultaneous effects of career development, competence, and performance allowance on employee performance improvement, as well as to determine the dominant variables affecting employee performance. The population consists of all Civil Servants at the Mojokerto City Transportation Office in 2023, totaling 43 individuals. The sample size matches the population due to saturation sampling. Data were collected using questionnaires and documentation, analyzed through percentage description and multiple linear regression. The multiple linear regression equation derived from the study is Y = 1.331 + 0.412 X1 + 0.192 X2 + 0.255 X3. Using SPSS 27, the hypotheses testing (t-test) showed partial significance values of 0.001 for career development (X1), 0.037 for competence (X2), and 0.002 for performance allowance (X3), all less than 0.05. Thus, it can be concluded that career development, competence, and performance allowance significantly influence employee performance improvement at the Mojokerto City Transportation Office. The analysis reveals that Career Development (X1), Competence (X2), and Performance Allowance (X3), with the dependent variable Employee Performance Improvement (Y) at the Mojokerto City Transportation Office, amount to 0.803, indicating a strong relationship as evidenced by the adjusted R-squared. The simultaneous hypothesis (F-test) is accepted, signifying a significant overall relationship between independent and dependent variables